Inulin-based colon targeted drug delivery systems: advancing site-specific therapeutics - Melese Getachew; Aytenew Atnaf; Mekdes Kiflu; Sefefe Birhanu Tizie; Getinet Nibret; Wubetu Yihunie Belay (Discover Materials)
Abstract Colon-targeted drug delivery has been used for the delivery of different drugs for the treatment of local diseases, as well as for the systemic delivery of proteins, therapeutic peptides, antiasthmatic drugs, antihypertensive drugs, and antidiabetic agents. Inulin is a polysaccharide mainly of plant origin that is indigestible by human enzymes and hence reaches the colon intact. Its unique properties, including biocompatibility, biodegradability, and selective breakdown by colonic microbiota along with its natural abundance, ease of production, and additional nutritional and health impacts make inulin a good candidate for drug delivery. The main aim of this review is to highlight the various formulation approaches for inulin-based colon-targeted drug delivery systems. Inulin-based solid dispersions, complexes, hydrogels, conjugates, microparticles, and nanoparticles are discussed in the review. Inulin and its various modification products could be considered a good vehicle for colon-targeted delivery of drugs belonging to various pharmacological classes to be used in both systemic and local routes. Although in vitro drug release studies have been conducted in many studies included in this review in vivo bioavailability and pharmacokinetics investigations are still lacking. Studies to optimize the drug-loading capacity, release kinetics, stability of inulin-based delivery systems, and scale-up of inulin-based colon-targeted formulations should be sought.